Qualidade de ensino-aprendizagem nas salas multisseriadas na educação do campo capixaba - Pimentel, Fabricia Alves da Silva (2014)
The demands and characteristics of the field capixaba multigrade schools are very diverse (maroon, fishermen, coastal, indigenous people, small farmers and large estates), but their characteristics are not considered to be developed curricula and teaching methodologies of thought. This study sought to identify characteristics of teaching proposals that best adequasse the demands of teaching in multigrade schools field. That were used for the references of scholars who re ected on popular education in particular on rural schools as Paulo Freire, Miguel Arroyo and others, as well as institutions like RACEFFAES working with teacher training in Pedagogy of Alternation and the Theory of apprenticeship significant Ausubel (1963) according to the interpretation of Moreira e Masini (1982) and Masini e Moreira (2008). The data collected and analyzed in the research pointed to the conclusion that children star in their knowledge when they are enrolled in schools where a curriculum developed is specifically designed for rural communities and teaching practices promote the active participation of students considering the previous knowledge as a point starting to build new knowledge, this is a teaching that enables meaningful learning for children.